PENGARUH KUALITAS PRODUK, MEREK, DAN HARGA TERHADAP MINAT BELI KONSUMEN PADA PEGGILINGAN PADI H. ANWAR DI DESA PUJOKERTO LAMPUNG TENGAH - Yayang Ahirian Fikri; Suryadi Suryadi (DINAMIKA: Jurnal Manajemen Akuntansi, Bisnis dan Kewirausahaan, 2019)
The purpose of this study is to study the positive, quality, brand, and price of consumer buying interest in PP. H. Anwar in Pujo Kerto, Central Lampung. The population of this research is PP consumers. H. Anwar. The sample decision making technique is accidental sampling by sampling for 15 days obtained 62 samples. The method used is a causal association by asking for a quantitative one, namely by interview or questionnaire. In this study the analysis tool used is multiple linear analysis to determine the dependent and independent variables with the SPSS 17 for Windows. The results of research conducted by researchers indicate the existence of product quality, brand, and price on consumer buying interest at the H. Anwar Rice Mill in Pujo Kerto, Central Lampung. Based on the analysis of the data obtained Fcount 306,834 ˃ Ftable 2.76 which is indicated by linear regression with a coefficient of determination (R2) 0941 which means that consumer spending is bought by variables of product quality, brand and price of 94.1% and 5.9% needed by other factors .